Pengaruh Pemberian berbagai Tingkat Protein terhadap Penampilan Puyuh Petelur - Lidy Herawaty; I.K. Amrullah; R.E. Abdelsamie (Buletin Ilmu Makanan Ternak, 1991)
A study was carried out to invastigate the effect of dietary protein levels with the same amino acid composition on egg production of Japanese quails. The protein levels were : 14%, 16%, 18%, 20%, and 22%. Feed and water were provided ad libitum.The experiment lasted from 5 weeks to 7 weeks of use. Protein level in diets increased hen-day egg production and feed conversion signifiantly (P<0.05). The 18% and 22% protein diets had the same effect on egg weight, feed consumption and feed conversion.It appears from this experiment that 18% protein diet is sufficient to increase egg production of japanese quails.